Improving Students’ Speaking Performance Through Digital Vlog Media - Fais Wahidatul Arifatin; Naajihah Mafruudloh; Anita Rahmah Dewi (Journal on Education, 2023)
This study aims to examine the students’ performance in speaking. The media that is used in this study is digital vlog media. The participants of this study are 33 students of Economic and Business faculty at Universitas Muhammadiyah Lamongan in the major study of Management. This is classroom action research that gathers the data from August to December in 2022. There are some difficulties in speaking performance as English is the students’ foreign language. This study is kind of quantitative research which researcher adapted pretest and posttest in analyzing the data using statistics of SPSS 25. The result shows that the students’ speaking performance is improved by performing in digital vlog. They got motivation how to improve their fluency and accuracy related to the tenses and also their pronunciations.